Near UV-Blue Excitable Green-Emitting Nanocrystalline Oxide. (19th May 2011) - Rodríguez-García, C. E.; Perea-López, N.; Hirata, G. A.
Abstract : Green-emitting Eu-activated powders were produced by a two-stage method consisting of pressure-assisted combustion synthesis and postannealing in ammonia. The as-synthesized powders exhibited a red photoluminescence (PL) peak located atλ = 616  nm when excited withλ = 395  nm UV. This emission peak corresponds to the 5 D0 → 7 F2 transition in Eu 3+ . After annealing in ammonia, the PL emission changed to an intense broad-band peak centered atλ = 500  nm, most likely produced by 4f 6 5d 1 →4f 7 electronic transitions in Eu 2+ . This green-emitting phosphor has excitation band in the near UV-blue region (λ = 300 –450 nm). X-ray diffraction analysis reveals mainly the orthorhombic EuAlO3 and Al2 O3 phases. Transmission electron microscopy observations showed that the grains are formed by faceted nanocrystals (~4 nm) of polygonal shape. The excellent excitation and emission properties make these powders very promising to be used as phosphors in UV solid-state diodes coupled to activate white-emitting lamps.